1977
DOI: 10.2135/cropsci1977.0011183x001700030016x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Gossypium barbadense L. Chromosomes 6 and 17 in the G. hirsutum L. Genome1

Abstract: The phenotypic contributions of two individual Gossypium barbadense L. chromosomes in a G. hirsutum L. background were evaluated. Monosomes 6 and 17 of G. hirsutum were used to transfer the individual intact homologues from a G. barbadense line (3‐79) into G. hirsutum. Following transfer, backcross‐derived substitution lines with 25 pairs of G. hirsutum chromosomes and one pair of G. barbadense chromosomes (6 or 17) were evaluated for the following agronomic properties: date of first flower; earliness; yield; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Study of several early versions of CS-B lines indicated that chromosome 6 of 3-79 confers a higher lint percentage, finer fiber, and later flowering relative to TM-1, and that chromosome 17 confers short fiber length (Kohel et al 1977). Ren et al (2002) mapped QTL for boll size, lint percentage, fiber length, and fiber elongation on chromosome 16 using 178 families from the cross of a CS-B line for chromosome 16 and TM-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of several early versions of CS-B lines indicated that chromosome 6 of 3-79 confers a higher lint percentage, finer fiber, and later flowering relative to TM-1, and that chromosome 17 confers short fiber length (Kohel et al 1977). Ren et al (2002) mapped QTL for boll size, lint percentage, fiber length, and fiber elongation on chromosome 16 using 178 families from the cross of a CS-B line for chromosome 16 and TM-1.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been extended with various modifications to several species. Methods for development of interspecific chromosome substitution in G. hirsutum were outlined by Endrizzi (1963), and several of the initially discovered G. hirsutum monosomics were used to substitute G. barbadense chromosomes into G. hirsutum (White et al 1967;Kohel et al 1977;Endrizzi et al 1984). To date, there have been no formal reports on long-term efforts to enhance productivity in Upland cultivars using interspecific chromosome substitution lines.…”
mentioning
confidence: 99%
“…Kohel et al (1977) and Ma and Kohel (1983) evaluated six cotton substitution lines and indicated some quantitative genes on the substituted chromosomes. Recently, we reported chromosome 25 from line 3-79 in a TM-1 background associated with longer and stronger fibers and lower micronaire as well and chromosomes 16 and 18 of 3-79 associated with decreased yields .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were focused on whole genome based analyzes (Cherry 1983;Kohel et al 1985;Dani and Kohel 1988;Wu et al 1995;Wang et al 1996a, b;Ye et al 2003). One of the advantages of using chromosome substitution lines is they can be used to associate traits of importance with specific chromosomes (Endrezzi 1963;Kohel et al 1977;Ma and Kohel 1983;Saha et al 2004Saha et al , 2006Jenkins et al 2006Jenkins et al , 2007McCarty et al 2006;Wu et al 2006). The previous studies on cotton chromosome substitution lines were focused on genetic analyzes of agronomic and fiber traits.…”
Section: Discussionmentioning
confidence: 99%